2018
DOI: 10.1021/acs.jpcc.7b11824
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing the Effect of Partial Oxide Formation on Single Silver Nanoparticle Electrodissolution

Abstract: The impact of heterogeneous surface oxide formation on the electrochemical performance of single silver nanoparticles is explored using in situ superlocalization optical microscopy. Silver nanoparticles are well-known to form a natural oxide layer on their surface, but the effect of this oxide layer on electrochemical reactions is not well understood. Here we track the temporal and spatial dependence of electrodissolution of single silver nanoparticles in order to study the role of surface oxide layers on elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
108
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 85 publications
(112 citation statements)
references
References 41 publications
(53 reference statements)
2
108
0
1
Order By: Relevance
“…[10] We also tracked the spatial origin of the scattering as a function of time and potential and found that NPs undergo either isotropic or anisotropic dissolution, due to the heterogeneous formation of Ag x O y layers on the particle surfaces. [10] We also tracked the spatial origin of the scattering as a function of time and potential and found that NPs undergo either isotropic or anisotropic dissolution, due to the heterogeneous formation of Ag x O y layers on the particle surfaces.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[10] We also tracked the spatial origin of the scattering as a function of time and potential and found that NPs undergo either isotropic or anisotropic dissolution, due to the heterogeneous formation of Ag x O y layers on the particle surfaces. [10] We also tracked the spatial origin of the scattering as a function of time and potential and found that NPs undergo either isotropic or anisotropic dissolution, due to the heterogeneous formation of Ag x O y layers on the particle surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…For example, surface oxides on Ag NPs can reduce SERS signals by damping the plasmondriven electromagnetic field enhancements near the particle surface. [10] Recently, we showed how nanoscale heterogeneity of surface oxide layers impacts the kinetics and morphology of single Ag NPs during electrodissolution using dark-field microscopy. [10] Recently, we showed how nanoscale heterogeneity of surface oxide layers impacts the kinetics and morphology of single Ag NPs during electrodissolution using dark-field microscopy.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[14] Although spectroscopic information is attainable,m uch of the work in the literature has focusedo nt he intensity of the scattered light from individual particles and its alteration during the course of their oxidation.T his allows the processes to be dynamically monitored and yields potentiali nsighti nto the reaction kinetics at the nanoscale. [15][16][17] Further development of holographict echniquest oe nable NP tracking in three dimensions has enabled the simultaneous in situ tracking of particlesadjacentt oa nd at an electrochemical interface. [18][19][20] Elsewhere, the trackingo fN P trajectories is aw ell-established techniquef or studies into areas including single NP growth or single NP reactions using as ingle NP spectrometer.…”
Section: Introductionmentioning
confidence: 99%